THE USE OF ANIMATED VIDEO TO TEACH WRITING NARRATIVE TEXT (RETAIN, 2015)
abstrak Untuk menguasai Bahasa Inggris, ada empat keahalian yang wajib untuk dipelajari khususnya bagi pelajar, ada empat jenis keahlian yaitu, mendengar, berbica, membaca dan menulis.Menulis adalah salah satu keahlian yang sulit untuk dikuasai dan salah satu keahlian yang penting untuk dikuasai. Menurut Byrne (1982) keahlian menulis sangatlah penting dan secara ironis, kita hanya bisa meningkatkan kebahasaan berbicara kita melalui menulis. Untuk bisa menulis dengan baik para murid diharuskan mengutarakan ide mereka kedalam bentuk teks dan tentunya teks itu wajib mempunyai struktur kebahasaan yang baik, disini guru dituntut untuk mengajar dengan berbagai cara, salah satunya adalah dengan mengajar mengunakan media untuk membangkitkan ketertarikan dan minat murid untuk menulis. Animated Video bisa menjadi media yang cocok untuk mengajar menulis narrative text. Di penelitian ini akan menjelaskan kegunanaan dan menjelaskan tanggapan siswa terhadap media ini. Di penelitian ini pengarang mengunakan penelitian dengan deskripsi kualitatif. Untuk mengumpulkan data penulis mengunakan field note, observasi checklist, respon dari siswa dan tugas menulis siswa. Penelitian dilakukan dua kali di SMP Ulul Albab Sidoarjo dengan subject penelitian adalah siswa kelas 9 pada kelas IX-C. hasil dari penelitian ini bahwa animated video pada saat proses belajar dan pembelajaran dapat meningkatkan ketertarikan murid pada pembelajar menulis narrative teks. Media ini membantu menciptakan suasana menyenangkan pada proses pengajaran, dari respon yang didapat melalui lembar quissionaire dapat diketahui bahwa kegunaaan media ini diproses pembelajaran mendapatkan respon positif dari siswa karena media ini dapat membantu siswa untuk menyelesaikan masalah dalam membuat karangan narrative text. Kata Kunci: isi, format, artikel. Abstract As to master English, there four skills that should be learned by the students, they are listening, speaking, reading and writing. Writing is one of the most difficult skills and important skill, which needed to be mastered. According to Byrne (1983) writing is important and paradoxically, we can only improve our spoken language by writing. To be able to produce a good writing the students need to express their ideas into a form of text and the text need to be well-organized.in here the teacher need a unique variations in teaching writing. The teacher has to find the media to make students’ interested to build their self confidence in writing. To solve the problem above, Animated Video can be a media that suitable in teaching writing narrative text. This research explains the use of Animated Video. Also the researcher describes the students’ responses towards the use of the media to write narrative text. In this research, researcher uses descriptive qualitative research. To gather the data researcher used field note observation checklist, questionnaires and student writing assignments. The researcher conducted the observation twice and it was done at SMP Ulul Albab Sidoarjo for the subject of the study was the students from ninth graders in IX – C. The result showed that animated video in teaching learning process could increases the students interest in writing narrative text, Animated Video helped to create pleasant atmosphere in teaching and learning process also they get more enthusiastic in the classroom, the students’ responses showed that they have a positive responses towards the use of Animated Video because the media could help them solve their problems in writing narrative text. Further more for the result of students’ writing assignment in term of the generic structure most of the students’ got excellent. According to the result above, it can be concluded that the use of Animated Video could overcome the students’ problems in writing narrative text especially in the term generic structure and stimulate their ideas. So they could compose good writing. Keywords: Animated Video, Teaching Writing, Narrative Text